2009
DOI: 10.1209/0295-5075/88/29901
|View full text |Cite
|
Sign up to set email alerts
|

Radiation damage in biological material: Electronic properties and electron impact ionization in urea

Abstract: PACS 71.20.Rv -Electron density of states and band structure of crystalline solids -Polymers and organic compounds PACS 79.20.Hx -Electron and ion emission by liquids and solids; impact phenomena -Electron impact: secondary emissionAbstract. -Radiation damage is an unavoidable process when performing structural investigations of biological macromolecules with X-rays. In crystallography this process can be limited through damage distribution in a crystal, while for single molecular imaging it can be outrun by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…Moreover, secondary electrons represent the main source of radiation damage following tissue irradiation. Thus knowledge of inelastic electron scattering in a dielectric, such as liquid water, is essential to fully understand how radiation affects living organisms [3][4][5] .…”
Section: Main Textmentioning
confidence: 99%
“…Moreover, secondary electrons represent the main source of radiation damage following tissue irradiation. Thus knowledge of inelastic electron scattering in a dielectric, such as liquid water, is essential to fully understand how radiation affects living organisms [3][4][5] .…”
Section: Main Textmentioning
confidence: 99%
“…Although proof of principle experiments have demonstrated that it is possible to obtain structural information from solid targets at low resolution (60 nm),29 issues like sample dynamics,30 and irreproducible scattering from bound solvent molecules31 will in practice probably limit the resolution of such experiments. Radiation damage to samples at atomic wavelengths is not completely understood either27, 32–36 and this may preclude obtaining high resolution structural information as well. Nevertheless, this technique may provide a powerful complement to IMS in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, urea crystals are a good model for protein nanocrystals, known to contain 30%-60% water. We refer to [5,9,16] and the supplementary material for further details of these calculations and how the model compares with experiments on diamond [17]. Considering m i to be the mass of electron i and r i the position of electron i with respect to the center of mass of all free electrons, the radius of gyration, used in Figure 2, is defined as…”
mentioning
confidence: 99%